Decremental responses in patients with motor neuron disease. Issue 11 (26th September 2017) - Alanazy, Mohammed H.; Hegedus, Janka; White, Chris; Korngut, Lawrence
Abstract: Objective: Involvement of the neuromuscular junction (NMJ) in amyotrophic lateral sclerosis (ALS) has been reported and is increasingly recognized as an important pathophysiological aspect. The relationship between decrement and clinical measures for possible application as a biomarker has not been comprehensively explored. Methods: We performed routine repetitive nerve stimulation (RNS) of three nerves on patients with ALS. We captured measures of muscle strength, grip strength, fatigability, and calculated slow vital capacity (SVC) rates of change assessing for associations. Results: In 42 subjects, 210 muscles were studied. Negative correlation was found between the percentage of decrement and compound muscle action potential (CMAP) amplitude. Approximately half of the patients with hand weakness did not have decrement. There was no significant correlation between decrement and handgrip fatigue, SVC < 80% predicted, or more rapid worsening of SVC over time. Conclusions: Abnormal decremental responses are well described in ALS. We report that the degree of decremental response does not correlate with the degree of weakness. Abnormal decrement is only rarely present in nerve–muscle pairs with normal motor power. Our findings did not support a correlation between abnormal decrement and clinical measures suggesting that RNS may not be useful as a biomarker to monitor ALS progression. Abstract : In patients with motor neuron disease, decremental responses with repetitive nerve stimulation showed no correlation with the degree of muscle weakness or other clinical measures. Thus, the decremental response is not a useful biomarker to monitor disease progression.